38.4k views
8 votes
What is the solution to the equation below?​

What is the solution to the equation below?​-example-1
User Pinny
by
5.3k points

2 Answers

4 votes

Answer:

x=-27

Explanation:

to understand this

you need to know about:

  • equation
  • PEMDAS

given:


  • - 8 = (x)/(3) + 1

to solve


  • x

let's solve:


step - 1 : define \\ - 8 = (x)/(3) + 1


step - 2 : \\ rewrite


(x)/(3) + 1= - 8


step - 3 : \\ subtract \: 1 \: from \: both \: sides


(x)/(3) + 1 - 1 = - 8 - 1


(x)/(3) = - 9


step - 4 : \\ multiply \: both \: sides \: by \: 3


(x)/(3) * 3 = - 9 * 3


\huge \therefore x = - 27

User Ninjasense
by
5.6k points
11 votes

Answer: x = -27

Explanation:

User Rszaman
by
5.8k points